Bleazard, T. A., Long, J. E., Pate, M. L., Lawver, R. G., Israelsen, C., & Hatch, R. (2018). Using Simulation in Auto-Guidance Technology Training among Farmers in Utah. Journal of Agricultural Systems, Technology, and Management, 29, 15-24. 15 Using Simu - Bleazard, Thomas A.; Long, Jennifer E.; Pate, Michael L.; Lawver, Rebecca G.; Israelsen, Clark; Hatch, Royce (Journal of Agricultural Systems, Technology, and Management, 2018)
The purpose of this descriptive-correlation study was to examine the variables associated with Utah farmers’ adoption of auto-guidance technologies and determine training preferences. Participants in this study engaged in an experiential training session utilizing an auto-guidance system comparable to those available for use in production agriculture settings. A survey was administered to identify auto-guidance technology adoption and farmers’ preferences for related training. A total of 61 participants completed the survey from two different Cooperative Extension Crop Schools in Utah. Half of the participants in this study (50.8%) indicated using auto-guidance technology in some form in their farming practices. Participants ranked three sections of the presentation by how effective they were at helping them learn about auto-guidance. Hands-on training on auto-guidance technology reported as the most effective training presentation component by the participants.